Exploring the e-cigarette e-commerce marketplace: Identifying Internet e-cigarette marketing characteristics and regulatory gaps. (1st November 2015) - Mackey, Tim K.; Miner, Angela; Cuomo, Raphael E.
Highlights: E-cigarette online vendors were reviewed for location, sales and marketing strategies, and age verification. Vendors heavily used social network services and used different sales promotion strategies to market products. Over 1/3rd of vendors had no detectable age verification process and those that did largely required only a click-thru verification. Abstract: Background: The electronic cigarette (e-cigarette) market is maturing into a billion-dollar industry. Expansion includes new channels of access not sufficiently assessed, including Internet sales of e-cigarettes. This study identifies unique e-cigarette Internet vendor characteristics, including geographic location, promotional strategies, use of social networking, presence/absence of age verification, and consumer warning representation. Methods: We performed structured Internet search engine queries and used inclusion/exclusion criteria to identify e-cigarette vendors. We then conducted content analysis of characteristics of interest. Results: Our examination yielded 57 e-cigarette Internet vendors including 54.4% ( n = 31) that sold exclusively online. The vast majority of websites (96.5%, n = 55) were located in the U.S. Vendors used a variety of sales promotion strategies to market e-cigarettes including 70.2% ( n = 40) that used more than one social network service (SNS) and 42.1% ( n = 24) that used more than one promotional sales strategies. Most vendors (68.4%, n = 39) displayed one or more health warnings on their website, but often displayed them in smaller font or in their terms and conditions. Additionally, 35.1% ( n = 20) of vendors did not have any detectable age verification process. Conclusions: E-cigarette Internet vendors are actively engaged in various promotional activities to increase the appeal and presence of their products online. In the absence of FDA regulations specific to the Internet, the e-cigarette e-commerce marketplace is likely to grow. This digital environment poses unique challenges requiring targeted policy-making including robust online age verification, monitoring of SNS marketing, and greater scrutiny of certain forms of marketing promotional practices.